Analisis Sistem Antrean untuk Mengoptimalkan Pelayanan pada Coffeeshop Teman Sejalan .Co di Karanganyar - Christe Wiwin Wikaningrum; Sunarso Sunarso (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
Teman Sejalan.co is a Coffeeshop located in Karanganyar and was established in December 2022. Operations in the Teman Sejalan.co Coffeeshop business certainly include from the initial order to pickup. This is related to the queuing system which must improve its service so that customers do not leave if there is a queue. This research uses the Single Channel Multiphase method which is in accordance with the current conditions of Teman Sejalan.co's servers and services. This data was obtained by going directly to the research object during the